Biomarkers in metastatic castration-resistant prostate cancer for efficiency of immune checkpoint inhibitors - Zixi Wu; Junbiao Zhang; Le Li; Zhihua Wang; Chunguang Yang (Annals of Medicine)
Almost all patients with prostate cancer progress to metastatic castration-resistant prostate cancer (mCRPC) despite initial responses. In cases where traditional first-line treatments prove ineffective, the potential of immune checkpoint blockade (ICB) therapy emerges as a promising approach for managing mCRPC. However, while immune checkpoint inhibitor monotherapy or combination therapy targeting cytotoxic T lymphocyte antigen 4 (CTLA-4) and/or programmed cell death-1 (PD-1)/PD-1 ligand 1 (PD-L1) axis has been regarded as the standard therapy in many solid tumours, mCRPC as ‘cold’ tumours are considered to be relatively resistant to ICB treatment. Encouragingly, recent evidence suggests that ICB therapy may be particularly beneficial in specific subgroups of patients with high PD-L1 tumour expression, high tumour mutational burden or high tumour microsatellite instability/mismatch repair deficiency. Better understanding of these predictive biomarkers could screen which patients are most likely to benefit. This review article examines biomarkers for screening patients potentially effective in immune checkpoint inhibitor therapy.